Teaching in Times of COVID-19: The Evaluation of Distance Teaching in Elementary and Secondary Schools in Germany - Schneider, Rebecca; Sachse, Karoline A.; Schipolowski, Stefan; Enke, Florian (Frontiers in Education, 2021)
To depict the situation during the school closures in spring 2020 that were implemented to contain the spread of COVID-19, we conducted a self-constructed online survey on distance teaching among teachers regarding their teaching practices in this new situation, the challenges they experienced, and the prerequisites for successful distance teaching. The sample consisted of voluntarily participating German elementary (n = 857) and secondary school teachers (n = 1,590) from a sample of randomly drawn schools in four federal states in Germany. We describe the main survey findings and examine the importance of different distance teaching aspects for teacher reports of students attaining their learning objectives and students’ learning progress during distance teaching. Our results particularly highlight the necessity for students and teachers to remain in contact in all the surveyed school types. In elementary school, regular contact between teachers and parents is similarly important. The key challenges highlighted inadequate digitalization, the participation of all students, and students’ motivation. Correspondingly, adequate technical equipment for schools, teachers, and students, together with teachers’ and students’ competence to use technical devices and digital media as well as students’ motivation to participate in distance learning were found to be necessary prerequisites for successful distance teaching. We conclude that efforts should be devoted to enabling teachers and students to better communicate using digital devices, for example, expanding the digital infrastructure in combination with training teachers and students in the use of technical devices and digital media.